Pengaruh Kepemimpinan Transformasional terhadap Kinerja Karyawan dengan Keterikatan Kerja sebagai Variabel Mediasi pada PT Rimba Hutani Mas - Dhea Anandiya Putri; Nur Hasanah; Fitri Chairunnisa (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to examine the effect of transformational leadership on employee performance with work engagement as a mediating variable at PT. Rimba Hutani Mas. The research applies a quantitative explanatory approach with a survey method involving 80 employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results reveal that transformational leadership has a positive and significant effect on both work engagement and employee performance. Furthermore, work engagement also demonstrates a positive and significant influence on employee performance and partially mediates the relationship between transformational leadership and employee performance. These findings indicate that inspirational, intellectual, and individualized leadership behaviors enhance employees’ enthusiasm, dedication, and absorption at work, which in turn lead to higher performance outcomes. The study contributes theoretically by reinforcing the transformational leadership model as an effective driver of employee engagement and performance within the forestry industry context. Practically, the results suggest that PT. Rimba Hutani Mas should strengthen leadership practices that emphasize vision, motivation, and personal attention to foster a more engaged and productive workforce.